Climate Adaptation Through Defense Diplomacy in the Indo-Pacific Region - Naqsabandiyah, Ayu Heryati (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2025)
This study investigates the contribution of defense diplomacy to climate change adaptation efforts in the Indo-Pacific region, focusing specifically on two prominent regional mechanisms: the ASEAN Defence Ministers’ Meeting (ADMM)—including ADMM Plus— and the Quadrilateral Security Dialogue (Quad). Employing Cottey and Forster’s conceptual framework of defense diplomacy—which emphasizes cooperative military engagement for building confidence and addressing shared security concerns—this paper analyzes how both platforms have formally integrated climate change into their agendas. While the climate-security nexus has often been underemphasized in traditional defense cooperation, this research finds that activities such as Humanitarian Assistance and Disaster Relief (HADR), military medicine, and information sharing serve as key operational components that indirectly strengthen regional climate resilience. Both ADMM and the Quad have acknowledged the significance of climate adaptation; yet, the Quad demonstrates a more coordinated approach with clearer strategies and programs. By highlighting these dynamics, this study underlines the growing importance of defense diplomacy as a mechanism for addressing non-traditional security threats in the Indo-Pacific. Keywords: Climate Change Adaptation, Defense Diplomacy, Indo-Pacific Penelitian ini mengkaji kontribusi diplomasi pertahanan terhadap upaya adaptasi perubahan iklim di kawasan Indo-Pasifik, dengan fokus khusus pada dua kerja sama pertahanan yaitu ASEAN Defence Ministers’ Meeting (ADMM)—termasuk ADMM Plus—dan Quadrilateral Security Dialogue (Quad). Dengan menggunakan kerangka konseptual diplomasi pertahanan dari Cottey dan Forster—yang menekankan kerja sama militer untuk membangun kepercayaan antar negara dan menangani isu-isu keamanan bersama—kajian ini menganalisis bagaimana kedua platform tersebut secara formal telah mengintegrasikan isu perubahan iklim ke dalam agenda kerja samanya. Meskipun hubungan antara isu iklim dan keamanan sering kali kurang mendapatkan perhatian dalam kerja sama pertahanan tradisional, penelitian ini mengemukakan argumen bahwa aktivitas seperti bantuan kemanusiaan dan penanggulangan bencana, military medicine, dan pertukaran informasi secara tidak langsung memperkuat ketahanan iklim di kawasan. Baik ADMM maupun Quad telah mengakui pentingnya adaptasi perubahan iklim; namun, Quad menunjukkan pendekatan yang lebih terkoordinasi dengan strategi serta program yang lebih jelas. Dengan menyoroti dinamika ini, studi ini menegaskan pentingnya diplomasi pertahanan sebagai mekanisme untuk menangani ancaman keamanan non-tradisional di Indo-Pasifik. Kata-kata kunci: Adaptasi Perubahan Iklim, Diplomasi Pertahanan, Indo-Pasifik